Homocysteine Aggravates Cortical Neural Cell Injury through Neuronal Autophagy Overactivation following Rat Cerebral Ischemia-Reperfusion - Zhao, Yaqian (Int J Mol Sci, 2016)
Elevated homocysteine (Hcy) levels have been reported to be involved in neurotoxicity after ischemic stroke. However, the underlying mechanisms remain incompletely understood to date. In the current study, we hypothesized that neuronal autophagy activation may be involved in the toxic effect of Hcy on cortical neurons following cerebral ischemia. Brain cell injury was determined by hematoxylin-eosin (HE) staining and TdT-mediated dUTP Nick-End Labeling (TUNEL) staining. The level and localization of autophagy were detected by transmission electron microscopy, western blot and immunofluorescence double labeling. The oxidative DNA damage was revealed by immunofluorescence of 8-Hydroxy-2′-deoxyguanosine (8-OHdG). Hcy treatment aggravated neuronal cell death, significantly increased the formation of autophagosomes and the expression of LC3B and Beclin-1 in the brain cortex after middle cerebral artery occlusion-reperfusion (MCAO). Immunofluorescence analysis of LC3B and Beclin-1 distribution indicated that their expression occurred mainly in neurons (NeuN-positive) and hardly in astrocytes (GFAP-positive). 8-OHdG expression was also increased in the ischemic cortex of Hcy-treated animals. Conversely, LC3B and Beclin-1 overexpression and autophagosome accumulation caused by Hcy were partially blocked by the autophagy inhibitor 3-methyladenine (3-MA). Hcy administration enhanced neuronal autophagy, which contributes to cell death following cerebral ischemia. The oxidative damage-mediated autophagy may be a molecular mechanism underlying neuronal cell toxicity of elevated Hcy level.